Conclusions drawn from the prosopographic analysis of canons belonging to cathedral chapters of medieval Hungary : 1200-1350 - Koszta, László (2012)
During the organisation of the Hungarian ecclesiastical system at the turn of the 11-12th centuries, cathedral monasteries came into being, initially populated by Benedictine monks and canons. The canons of cathedral chapters in Hungary lived in vita communis until the end of the 12th century. Henceforth, cathedral chapters were regarded as independent legal entities. The 13th century was a period of expansion for the canons in Hungary. In the first part of the century, canons, with the help of the king and bishops, extended their remarkable influence over the country’s clergy and obtained a considerable share in the tithe income of country churches. In the second half of the 13th century and having established their wealth and consciousness, the canons also attempted to strengthen their position in opposition to prelates. This period may be characterised by the clashes between bishops and cathedral chapters. The latter were appointed by the king from the ranks of court priests, which seriously limited the social status of canons who were unable to develop a consistent policy against the prelates. A prosopographical analysis of this ecclesiastic group leads to several conclusions, as presented in this paper.